2017
DOI: 10.1080/01635581.2018.1380204
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Chemopreventive, Antiproliferative, and Superoxide Anion Scavenging Properties ofKluyveromyces marxianusandSaccharomyces cerevisiae var. boulardiiCell Wall Components

Abstract: This study investigated the cancer chemopreventive, the antiradical, and the antiproliferative properties of polysaccharides extracts from cell wall of Saccharomyces boulardii and Kluyveromyces marxianus. β-glucan, mannan, and chitin were also quantified to identify the most important extract responsible for these biological properties. Soluble and insoluble glucans as well as mannoprotein were extracted from cell wall using single hot-alkaline method. Superoxide anion scavenging (antiradical capacity), NAD(P)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 57 publications
0
23
0
Order By: Relevance
“…boulardii on cell growth, development and apoptosis, this yeast was thoroughly spread over the HT-29 cells by using 4′,6-diamidino-2-phenylindole (DAPI) dye and 3-(4,5-dimethylthiazoyl-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay. The expression profiles of PTEN/caspase-3, Bclxl and RelA genes were evaluated by real-time PCR [ 94 ]. After 24 h, the activity of PTEN and caspase-3 gene was increased.…”
Section: Mechanisms Of Action Of S Cerevisiae Var ...mentioning
confidence: 99%
See 1 more Smart Citation
“…boulardii on cell growth, development and apoptosis, this yeast was thoroughly spread over the HT-29 cells by using 4′,6-diamidino-2-phenylindole (DAPI) dye and 3-(4,5-dimethylthiazoyl-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay. The expression profiles of PTEN/caspase-3, Bclxl and RelA genes were evaluated by real-time PCR [ 94 ]. After 24 h, the activity of PTEN and caspase-3 gene was increased.…”
Section: Mechanisms Of Action Of S Cerevisiae Var ...mentioning
confidence: 99%
“…boulardii yeast showed anti-neoplastic effects on rat colon cancer cells when treated with dimethylhydrazine and S. cerevisiae var. boulardii orally [ 94 ]. Chen et al reported that S. cerevisiae var.…”
Section: Mechanisms Of Action Of S Cerevisiae Var ...mentioning
confidence: 99%
“…Antiproliferative properties were reported for both S. cerevisiae and probiotic S. cerevisiae var. boulardii supernatant (Fortin et al., 2018a, 2018b). It is worthwhile to declare that we observed SBS decreased the cell viability of EPG and RDB cells.…”
Section: Resultsmentioning
confidence: 99%
“…Cell wall components of specific strains of Kluyveromyces marxianus and Saccharomyces cerevisiae var. boulardii have been reported to act as cancer chemo-preventive and antiproliferative and showed superoxide anion scavenging properties [ 85 ]. Probiotic cultures preventing the adherence of pathogens in the gut are considered to be live bio-therapeutics [ 86 ].…”
Section: Use Of Probiotics For Pharmaceutical Propertiesmentioning
confidence: 99%